GPS Satellite Advancements and its Future - Kochhar, Gopal; Rajaan, Rajesh; Gupta, Sunil (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 7 No 1 (2020): Journal of Advanced Research in Instrumentation and Control Engineering(ISSN: 2456-1398), 2020)
This paper gives an brief introduction of global positioning system, its generations, the future and progressions that are attained by the GPS and tracking systems. The latest usage and the comparative study of the GPS satellites that are launched and are operational till date. How to cite this article: Kochhar G, Agarwal A, Athaiya A et al. GPS Satellite Advancements and its Future. J Adv Res Instru Control Engi 2020; 7(1): 1-4. DOI: https://doi.org/2010.24321/2456.1398.202001